1986
DOI: 10.2307/3344795
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Exposure to Classical Music on the Musical Preferences of Preschool Children

Abstract: Musical preferences of 45 preschool children (mean age 4 years, 7 months) were assessed in a short-range longitudinal study incorporating a pre- and posttest experimental design. Six classical and two popular pieces were evaluated. All children liked all the pieces during the pretest. During the 10 months that elapsed between pre- and post-testing, an experimental group ( n = 21) received weekly 45-min classes in appreciation of classical music during which they listened to classical music, sang classical them… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
37
1
2

Year Published

1987
1987
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 17 publications
1
37
1
2
Order By: Relevance
“…Other local child-participants also mentioned Twins-a female duet group who sings another popular cartoon theme song named Pretty cure. Indeed, such results are consistent with Peery and Peery's (1986) research, which showed that popular music is preschoolers' most preferable music genre. Due to the lucrative but competitive Cantopop market in HKSAR (Ho 2003a;Ogawa 2004), theme songs are further broadcast on a frequent and regular basis over local radio channels as well in order to boom the sales of related audio and/or audiovisual products.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Other local child-participants also mentioned Twins-a female duet group who sings another popular cartoon theme song named Pretty cure. Indeed, such results are consistent with Peery and Peery's (1986) research, which showed that popular music is preschoolers' most preferable music genre. Due to the lucrative but competitive Cantopop market in HKSAR (Ho 2003a;Ogawa 2004), theme songs are further broadcast on a frequent and regular basis over local radio channels as well in order to boom the sales of related audio and/or audiovisual products.…”
Section: Discussionsupporting
confidence: 92%
“…However, only a limited number of studies were found to be focused in the field of early childhood education. Among these limited early childhood studies, most were mainly concerned with young children's preferences for musical styles or genres (e.g., Cassidy and Geringer 1999;Hargreaves et al 2006;Peery and Peery 1986;Rogers 1957;Roulston 2006). Very few of the studies explored young children's preferences for group musical activities particularly in early childhood settings (e.g., Bowles 1998;Harrison and O'Neill 2000;Murphy and Brown 1986;Nolin 1973;Temmerman 1995Temmerman , 2000.…”
Section: Introductionmentioning
confidence: 99%
“…Baker (1980) and Flowers (1981) reported encountering difficulties in using words with preschool and elementary subjects. Since young children do not always possess the vocabulary or reading skills needed to deal with verbal or numerical choices, attitude measurement has often consisted of children choosing a cartoon face to represent feelings toward a stimulus or to respond to a question (Byres, 1994;Giomo, 1993;Kratus, 1993;LeBlanc, Sims, Siivola, & Obert, 1996;Peery & Peery, 1986;Sims, 1987). Another advantage of using pictographic scales as a model of evaluation is that "listening to music determines regions of possible meaning concerning which verbal language is at once too precise and too lax" (Frances, 1988, p. 235).…”
mentioning
confidence: 99%
“…For example, repeated passive exposure to music styles tends to increase liking or preference for those styles through increased familiarity (Getz, 1966;Krugman, 1943;Peretz, Gaudreau, & Bonnel, 1998;Schuckert & McDonald, 1968;Trammell, 1977), yet the effects of repeated passive exposure or no exposure as compared to instruction on music preferences are ambiguous. Some researchers have indicated that guided listening and other instructional methods are no more effective in increasing students' music preferences than repetition or no exposure (Bartlett, 1973;Geringer & Nelson, 1980;Prince, 1974;Zumbrunn, 1972), whereas other studies (Bradley, 1972;Peery & Peery, 1986) have revealed an increase in preference as a consequence of instruction. When two or more specific instructional approaches have been compared, no approach seems to substantially increase students' preferences for a particular music style (Burns, 1995;Gross, 1984;Sims, 1986).…”
Section: Instruction and Music Preferencementioning
confidence: 99%